Invasive Drosophila suzukii facilitates Drosophila melanogaster infestation and sour rot outbreaks in the vineyards. Issue 3 (29th March 2017) - Rombaut, A.; Guilhot, R.; Xuéreb, A.; Benoit, L.; Chapuis, M. P.; Gibert, P.; Fellous, S.
Abstract : How do invasive pests affect interactions between members of pre-existing agrosystems? The invasive pest Drosophila suzukii is suspected to be involved in the aetiology of sour rot, a grapevine disease that otherwise develops following Drosophila melanogaster infestation of wounded berries. We combined field observations with laboratory assays to disentangle the relative roles of both Drosophila in disease development. We observed the emergence of numerous D. suzukii, but no D. melanogaster flies, from bunches that started showing mild sour rot symptoms days after field collection. However, bunches that already showed severe rot symptoms in the field mostly contained D. melanogaster . In the laboratory, oviposition by D. suzukii triggered sour rot development. An independent assay showed the disease increased grape attractiveness to ovipositing D. melanogaster females. Our results suggest that in invaded vineyards, D. suzukii facilitates D. melanogaster infestation and, consequently, favours sour rot outbreaks. Rather than competing with close species, the invader subsequently permits their reproduction in otherwise non-accessible resources and may cause more frequent, or more extensive, disease outbreaks.